2014
DOI: 10.1111/jpim.12235
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Suppliers' Technical Contributions to New Product Advantage: Substitution and Configuration Options

Abstract: Current theory lacks clarity on how different kinds of resources contribute to new product advantage, or how firms can combine different resources to achieve a new product advantage. While several studies have identified different firm‐specific resources that influence new product advantage, comparatively little research has explored the contribution of strategic supplier resources. Combining resource‐based and relational perspectives, this study develops a theoretical model investigating how a strategic suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 122 publications
(198 reference statements)
0
33
0
Order By: Relevance
“…The present study is part of a broader research effort to investigate supplier involvement in NPD. Other papers drawing on this data set include Lawson and Potter (2012), Potter and Lawson (2013) and Lawson, Tyler, and Potter (2014). Using a database on R&D-intensive firms maintained by the UK Department of Trade & Industry, we survey 1700 medium-to-large manufacturing firms.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…The present study is part of a broader research effort to investigate supplier involvement in NPD. Other papers drawing on this data set include Lawson and Potter (2012), Potter and Lawson (2013) and Lawson, Tyler, and Potter (2014). Using a database on R&D-intensive firms maintained by the UK Department of Trade & Industry, we survey 1700 medium-to-large manufacturing firms.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In parallel with this trend, research from the supply chain management literature has found that involving suppliers in the innovation process can enhance the potential for positive outcomes to emerge from inter-organizational NPD projects (Liker and Choi, 2004;Aoki and Lennerfors, 2013). Supplier involvement in NPD enables firms to access supplier resources and innovation capabilities in a way that is conducive to the implementation of eco-innovation (Lawson et al, 2015). In particular, studies have found that Toyota frequently uses early supplier involvement to integrate its suppliers into the fuzzy front end of the NPD process (Dyer and Nobeoka, 2000;Aoki and Lennerfors, 2013).…”
Section: The Natural Resource-based View (Nrbv) and Eco-innovationsmentioning
confidence: 99%
“…The analysis focuses on collaborations with suppliers as an example of interorganizational collaboration. Suppliers are a potential and easily accessible source of solutions to specific problems linked to new product development rather than being a source of generic new ideas and technological options, which may instead have long lags to market (Lawson, Tyler, and Potter, ; Un et al, ; Van Echtelt, Wynstra, Van Weele, and Duysters, ). The growing importance of suppliers as partners in the innovation process is exemplified by a quote from Biswairan Sen, Vice President of Procurement at Unilever, who stated that from 2012 and 2014, “[…] about 70% of our innovations have been contributions from our suppliers” (Degun, ).…”
Section: Introductionmentioning
confidence: 99%